2015
DOI: 10.1021/acs.biochem.5b00876
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Rev–RNA Interactions in HIV-1 Rev–RRE Assembly

Abstract: The HIV-1 protein Rev facilitates the nuclear export of intron-containing viral mRNAs by recognizing a structured RNA site, the Rev-response-element (RRE), contained in an intron. Rev assembles as a homo-oligomer on the RRE using its α-helical arginine-rich-motif (ARM) for RNA recognition. One unique feature of this assembly is the repeated use of the ARM from individual Rev subunits to contact distinct parts of the RRE in different binding modes. How the individual interactions differ and how they contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Nonetheless, with the methods used, it is difficult to discriminate quantitatively between specific and nonspecific binding. The relative contributions of enthalpy and entropy of WT‐IIB are roughly similar to what has been reported for a similar interaction in detailed thermodynamic study characterizing a Rev ARM peptide binding to IIB and IA RRE RNAs. Jayaraman et al report dissociation constants ranging from 0.02 nM at 283 K and 100 mM KCl to 16.3 nM at 303 K and 300 mM KCl, approaching the dissociation constant of 22 ± 8 nM reported here for WT‐IIB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, with the methods used, it is difficult to discriminate quantitatively between specific and nonspecific binding. The relative contributions of enthalpy and entropy of WT‐IIB are roughly similar to what has been reported for a similar interaction in detailed thermodynamic study characterizing a Rev ARM peptide binding to IIB and IA RRE RNAs. Jayaraman et al report dissociation constants ranging from 0.02 nM at 283 K and 100 mM KCl to 16.3 nM at 303 K and 300 mM KCl, approaching the dissociation constant of 22 ± 8 nM reported here for WT‐IIB.…”
Section: Resultsmentioning
confidence: 99%
“…Other arginines form ionic interactions with the phosphates of the backbone, and Trp45 is not important for binding isolated IIB, but required for multimeric binding of Rev to larger regions of RRE . Importantly, the mutually inducted fit of Rev ARM and IIB binding appears to extend through complex and cooperative binding of multiple Rev proteins to other binding sites in RRE …”
Section: Introductionmentioning
confidence: 99%
“…This oligomeric complex has been reconstituted as a Rev hexamer on the 242‐nt RRE . Although each subunit of the Rev oligomer contains identical ARMs, the mode of RNA recognition at each binding site in the RRE is unique . Structural and thermodynamic studies of the three well‐characterized binding sites (Stem‐loop IIB, Stem IA and Junction IIABC) have revealed that different sets of Rev residues make varied contacts to the RNA in each case (Figure (a)).…”
Section: Plastic Assembly Of the Rev Oligomermentioning
confidence: 99%
“…Specific Rev binding was also observed with an isolated stem IA hairpin (Daugherty et al, 2008), which contains a similar asymmetric purine-rich internal loop as in stem IIB, suggesting that at least a portion of binding specificity is dictated by the RNA structure (Daugherty et al, 2008). Stem IA likely forms an intermediate binding site in the overall assembly of the Rev/RRE RNP (Bai et al, 2014; Jayaraman et al, 2015). Interestingly, although each Rev subunit uses a single alpha-helical ARM to bind to the RRE, the mode of RNA recognition is unique to each site (Daugherty et al, 2008; Jayaraman et al, 2015).…”
Section: The Rre Provides the Scaffold And Dictates The Conformation mentioning
confidence: 99%
“…Stem IA likely forms an intermediate binding site in the overall assembly of the Rev/RRE RNP (Bai et al, 2014; Jayaraman et al, 2015). Interestingly, although each Rev subunit uses a single alpha-helical ARM to bind to the RRE, the mode of RNA recognition is unique to each site (Daugherty et al, 2008; Jayaraman et al, 2015). Mutagenesis revealed that Rev utilizes different amino acids to recognize stem IIB and stem IA, in combination with structural studies that corroborated different binding strategies for each site (Daugherty et al, 2008).…”
Section: The Rre Provides the Scaffold And Dictates The Conformation mentioning
confidence: 99%